2022
DOI: 10.1177/00302228221082429
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Death Anxiety and Death-Related Depression Levels in the Elderly During the COVID-19 Pandemic

Abstract: The aim of the study is to determine the levels of death anxiety and death-related depression in the elderly during the COVID-19 pandemic. The sample of the descriptive-relational study includes 344 elderly people registered in a family health center. It was determined that the most dreaded fear reported by the elderly who got COVID-19 infection was death, and there was a highly significant positive correlation between death anxiety and death-related depression ratings of the elderly and that as the average de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Among the reasons why COVID-19 is considered a threat, the possibility of high-income elderly people and even healthy adults to die is highlighted (Campiolo et al, 2020). Erbesler and Demir (2022) identified that death was pointed out as the biggest fear among the elderly people who had been diagnosed with COVID-19. The fact that COVID-19 is an infectious disease, high mortality rates, uncertainties about the future and classification of the elderly as part of the risk group can cause these people to think about death, raising the levels of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons why COVID-19 is considered a threat, the possibility of high-income elderly people and even healthy adults to die is highlighted (Campiolo et al, 2020). Erbesler and Demir (2022) identified that death was pointed out as the biggest fear among the elderly people who had been diagnosed with COVID-19. The fact that COVID-19 is an infectious disease, high mortality rates, uncertainties about the future and classification of the elderly as part of the risk group can cause these people to think about death, raising the levels of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…A surprising finding for the COVID fear scale was that as the fear of COVID infection increased, self-care decreased which is the opposite of what would be expected and difficult to interpret (Sharifi et al, 2021). In a similar study, death anxiety and death-related depression were correlated with each other (N= 344) (Erbesler et al, 2022). This was not surprising given that depression and anxiety are typically comorbid.…”
Section: Fear Of Covid and Fear Of Deathmentioning
confidence: 93%
“…This review concludes that sex, specifically being female, [25][26][27]31,32,38,45,50,62,63 is associated with an increased likelihood of having depressive symptoms. This finding is consistent with pre-pandemic studies, [64][65][66] as well as a study conducted during the previous SARS-CoV-1 outbreak.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 95%
“…Stress-related factors and feelings or worries related to the pandemic: COVID-19 concerns, 31,[40][41][42] immediate distress related to COVID-19, 43 feeling very vulnerable to the risk of contracting COVID-19, 31,35,44,45 fear of infecting other people 45 and feelings regarding the high mortality due to COVID-19 46 are encompassed in this domain and were associated with higher rates of depression. Studies related to the previous outbreak of SARS-CoV-1 in 2002 also reported an association between depressive symptoms and concerns about the future 47 and high perceived threat of mortality.…”
Section: Factors Related To the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation